Molecular Dynamics Simulations of High‐Performance, Dissipationless Desalination across Self‐Assembled Amyloid Beta Nanotubes. Issue 16 (20th January 2023) - Liu, Yu‐Cheng; Yang, Dah‐Yen; Deng, Jin‐Pei; Sheu, Sheh‐Yi
Abstract: Climate change is causing droughts and water shortages. Membrane desalination is one of the most widely employed conventional methods of creating a source of clean water, but is a very energy‐intensive process. Membrane separation requires high salt selectivity across nano‐channels, yet traditional techniques remain inefficient in this regard. Herein, a bioinspired, chemically robust, amyloid–fibril‐based nanotube is designed, exhibiting water permeability and salt rejection properties capable of providing highly efficient desalination. Molecular dynamics simulations show that nano‐dewetting facilitates the unidirectional motion of water molecules on the surface of amyloid beta (Aβ) sheets owing to the ratchet structure of the underlying potential surface and the broken detailed balance. The water inside the self‐assembled Aβ nanotube (ABNT) overflows, while the passage of salts can be blocked using amphiphilic peptides. The designed nanofilter ABNT shows 100% desalination efficiency with perfect NaCl rejection. The production of ≈2.5 tons of pure water per day without any energy input, which corresponds to a water flux up to 200 times higher than those of existing commercial methods, is assessed by this simulation method. These results provide a detailed fundamental understanding of potential high‐performance nanotechnologies for water treatment. Abstract : A high‐throughput desalination apparatus is designed consisting of an amyloid beta (Aβ)‐sheet having a ratchet potential, allowing unidirectional flow. A self‐assembled Aβ nanotube (ABNT) exhibits a water pump; hence, water flows without requiring external energy input. An ABNT membrane‐supported device allows us to build a nanofluidic desalination system.